Visual Impact of Color on Children's Excitement Development, Making Exterior Wall Mural at Taruna Bakti Kindergarten Bandung - Lois Denissa; Rosida Tiurma Manurung; Olga Catherina Pattipawaej; Izmet Zainal Effendi; Iman Budiman (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2022)
This Mural Painting Community Service was carried out in collaboration with the Bandung Taruna Bakti Kindergarten School with Fine Arts Study Program, Maranatha Women's Family Association, and Spectrum Wall Paint Industry as a material sponsor. The purpose of this mural creation activity is to bring the colorful space closer to the children's play area during breaks so that it have a positive impact on the children mental development. Children at the golden age of 0-8 years old have a rapid growth in cognitive, motoric and psychosocial aspects. The results of the study stated that children who received color stimulation continuously at the age of golden age would grow up to be strong individuals in facing various challenges and problems of life. The method used in this community service was to sketch the stylized forms of flora and fauna directly onto the wall like graffiti painting by using permanent black graffiti spray paint. Furthermore, the sketches of flora and fauna stylized forms are filled with striking colors, various textures according to their respective creativity with tinting technology wall paint media that is resistant to weather. The success of this activity is expected to be a driving force for adults to care for the kindergartens at their early childhood, so the next generation would have higher quality in the future.